Locus of Control as a Moderator in the Relationship Between Job Satisfaction and Organizational Commitment: a Study of Indian It Professionals - Chhabra, Bindu (Organizations and Markets in Emerging Economies, 2019)
In recent times, increasing interest has been shown by OB and HR practitioners in the area of organizational commitment (OC). This interest stems from the fact that the committed workforce is considered beneficial for organizational functioning and effectiveness. The present study was conducted to explore the direct relationship of job satisfaction and locus of control (LOC) on organizational commitment. The purpose of the study was also to see if locus of control moderates the relationship between job satisfaction and organizational commitment. The study was conducted using structured questionnaires for measuring the above mentioned variables. The sample of the study was 449 Indian IT professionals. Hierarchical multiple regression showed that job satisfaction and internal locus of control was positively related to organizational commitment. Also, locus of control was found to moderate the relationship between job satisfaction and organizational commitment such that the relationship was stronger for internals than for externals. The present study has important implications for human resource development in the IT sector. Managers should use strategies to achieve high job satisfaction and organizational commitment. They must be aware of the moderating role which different personality attributes play in the relationship between job satisfaction and organizational commitment.